ChemInform Abstract: Intramolecular Sulfonylamidomethylation of 2‐(2‐Naphthyl) and 2‐(1‐Naphthyl)ethanesulfonamides: Synthesis of New Class of Naphthosultams. Issue 33 (August 2015) - Sasiambarrena, Leandro D.; Canepa, Alicia S.; Luna, Constanza N.; Bravo, Rodolfo D.
Abstract The amberlyst XN‐100 catalyzed reactions of sulfamides (I) and (IV) with trioxane (II) gives access to novel naphthosultams with high regioselectivity.